Taxonomic contribution to the knowledge of the oribatid mite family Scheloribatidae (Acari, Oribatida), with description of three new species from Vietnam - Ermilov, Sergey G.; Salavatulin, Vladimir M. (Zootaxa, 2023)
Three new oribatid mite species of the family Scheloribatidae (Oribatida)—Dometorina (Dometorina) robusta sp. nov., Phylloribatula latiseta sp. nov., Scheloribates (Scheloribates) paraflagellisetosus sp. nov.—are described, based on adults collected from tree branches of Dipterocarpus alatus in southern Vietnam. Representatives of Dometorina (Dometorina) and Phylloribatula are recorded in the Vietnamese fauna for the first time. An identification key to the known species of Phylloribatula is provided.